Cytokines: the yin and yang of vitiligo pathogenesis. (1st February 2019) - Singh, Mala; Kotnis, Ashwin; Jadeja, Shahnawaz D.; Mondal, Anushree; Mansuri, Mohmmad S.; Begum, Rasheedunnisa
ABSTRACT: Introduction : Dysregulation of melanocyte function is associated with vitiligo, an idiopathic autoimmune hypopigmentary skin disorder, caused by the selective destruction of melanocytes. Cytokines, the key mediators of immune response, which are pivotal in maintaining immune homeostasis, are crucial in vitiligo pathogenesis. Several studies indicate that there is an imbalance between pro- and anti-inflammatory cytokines in the skin and serum of vitiligo patients. Areas covered : In this comprehensive review, we have summarized the correlation of cytokine imbalance and vitiligo pathogenesis, its role in melanocyte biology, and its impact on vitiligo treatment. We have integrated various published reports on the levels of major cytokines from skin and serum samples of vitiligo patients. We have also discussed the role of endoplasmic reticulum and oxidative stress on cytokine imbalance and vice versa leading to destruction of melanocytes. Expert commentary : The review reflects that dysregulation of cytokines is multifactorial, ranging from genetic predisposition to altered protein expression relevant to vitiligo pathogenesis. We emphasize that cytokine imbalance in systemic and skin microenvironment plays a crucial role in vitiligo pathogenesis and has promising potential as therapeutic targets for vitiligo.